Prediction of genetic potential of segregating upland rice population - Santos, Patrícia Guimarães; Soares, Antônio Alves; Ramalho, Magno Antonio Patto (Pesquisa Agropecuaria Brasileira, 2001)
This work aimed to evaluate the Jinks & Pooni's method to predict genetic potential of the segregating upland rice population and to study the effect of the segregating population x environment interaction in the selection of those populations. In this work 23 segregating populations of upland rice with two checks were used. They were evaluated in a 5x5 lattice, with three replicates, in the agricultural year of 1996/97. The populations were conducted in two sites in Minas Gerais State, Brazil, Lavras and Patos de Minas, at three distinct sowing times. The results found in relation to the probability of extracting superior lines from a certain population indicated as the most promising the populations CNAx 5496 and CNAx 6001 and as the least promising CNAx 6063 and CNAx 6102. The Jinks & Pooni's method was a feasible alternative in the choice of populations most promising permitting the breeder to concentrate his effort in the evaluation of a higher family. The occurrence of the segregating population x sowing time and site x sowing time interactions showed the importance of evaluating the populations in more than one environment. The choice of the populations which presented a steady behavior against the environmental drifts is an important step within an improvement program and the chance to obtain success in this phase rises.